The ecosystem services of animal microbiomes. Issue 8 (12th March 2018) - McKenney, E. A.; Koelle, K.; Dunn, R. R.; Yoder, A. D.
Abstract: Microbiologists often evaluate microbial community dynamics by formulating functional hypotheses based on ecological processes. Indeed, many of the methods and terms currently used to describe animal microbiomes derive from ecology and evolutionary biology. As our understanding of the composition and functional dynamics of "the microbiome" grows, we increasingly refer to the host as an ecosystem within which microbial processes play out. Even so, an ecosystem service framework that extends to the context of the host has thus far been lacking. Here, we argue that ecosystem services are a useful framework with which to consider the value of microbes to their hosts. We discuss those "microbiome services" in the specific context of the mammalian gut, providing a context from which to develop new hypotheses and to evaluate microbial functions in future studies and novel systems.